Answer:
6x + 1
3x + 3
6x + 9
Explanation:
1)
To find the missing number, compare both sides of the equation. If the variable terms are the same and the constant terms are different, then the equation has no solutions.
2x + 9 + 3x + x = _x +_
6x + 9 = _x + _
6x + 9 = 6x + 1
2)
To find the missing number, compare both sides of the equation. If the variable terms are the different and the constant terms are either different or same, then the equation has one solution.
2x + 9 + 3x + x = _x + _
6x + 9 = _x + _
6x + 9 = 3x + 3
3)
When equation is true for every possible value of x.
To find the missing number, compare both sides of the equation. If the variable terms are the same and the constant terms are same, then the equation has no solutions.
2x + 9 + 3x + x = _x + _
6x + 9 = _x + _
6x + 9 = 6x + 9
6x = 6x +9 -9
6x = 6x
6x/6 = x
x = x